Cost-effectiveness analysis of water policy measures for nutrients: A regional model - Vincent Linderhof; Stijn Reinhard (European Regional Science Association (ERSA), 2010)
The Water Framework Directive (WFD) requires member states to implement abatement measures to ensure a good ecological and chemical status of all surface and ground waters by 2015. One of the main challenges in the implementation of the WFD is the selection of cost-effective programs of measures to reach these water quality objectives for all water bodies. Assessment of the river basin management plans teaches us that nutrient emission in many water bodies in the Netherlands will not comply with the WFD requirements in 2015. Since agriculture is largely responsible for these nutrient emissions, a number of agricultural technical measures with respect to reduction of nutrient emissions is suggested such as buffer strips, and natural banks, for instance. This paper presents the results of the economic optimization model, called RegiOptimizer, which calculates the lowest economic costs of implementing pollution abatement measures to reach the WFD water quality targets for nutrients at the water body level. The RegiOptimizer model includes two substances namely N and P. One of the key features of the regiOptimizer is that it includes explicitly hydrological relationships to translate nutrient emissions into N and P concentration levels of surface water. In particular, the model takes into account the impact of measures implemented upstream and their impacts on N and P concentrations in surface water downstream. In addition, it takes into account interrelationships between measures for N and P emissions, and it includes tradeoffs between abatement measures for agricultural and non-agricultural sectors. The model is applied to the Beerze and Reusel river basin in the south of the Netherlands which is bordered by Belgium. The first results with a limited number of pollution abatement measures indicate that the total annual costs will amount approximately 1.7 mln Euro for the baseline situation. Alternatively, if Belgium would comply to the WFD targets for nutrients, the total annual costs for pollution abatement measures in the Beerze and Reusel river basin would decline to 1.3 mln Euro. Even though water quality improves for several water bodies many are still too polluted due to the limited number of pollution abatement measures.
Keywords: 330; Cost-effectiveness analysis; Nutrient concentrations reduction; Watereconomic model; The Netherlands